Analiza wybranych własności metody MART - Trzęsiok, Joanna (The analysis of some properthies of MART, 2006)
In the paper MART - the multiple additive regression trees are presented. This is one of the boosting methods. It seeks for a linear combination of base functions which are regression trees. The final model in the stagewise approach is obtained by improving the performance of the components in each iteration and has a high accuracy. The primary goal of this paper was to show that MART is resistant against noise and outliers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 510-518